Estudio de la actividad antimicrobiana de ciprofloxacina y estreptomicina en los géneros escherichia y arcobacter aisladas de agua y alimentos de origen animal - Vásconez Vinza, Felipe Sebastián (2020)
In this investigation the antimicrobial activity of Ciprofloxacin and Streptomycin in the Escherichia and Arcobacter genera isolated from water and food of animal origin was studied, so we considered; resuscitate microorganisms of the genera under study, extract DNA from the isolates and amplify the DNA obtained by PCR (Polymerase chain reaction). And finally analyze the Antimicrobial Activity of Ciprofloxacin and Streptomycin on the strains obtained. For the current investigation of the 60 samples of cheese, water and meat isolates that were extracted from their DNA, 60 were positive for bacteria of the genera Arcobacter and Escherichia by means of the PCR test. In addition, the study of the antimicrobial activity of Ciprofloxacin and Streptomycin was performed by the Kirby-Bauer technique for which we could observe that for the treatment (T1) with a minimum concentration of drug (1 µg), 100% bacterial resistance was exhibited by the two genera under study against Streptomycin and Ciprofloxacin, it was shown that the T2 treatment with a concentration of 2 µg, is the minimum concentration of drug necessary to produce a partial inhibition of the bacteria (10/20 cases); for T0 (control), T3 and T4, no isolates of Escherichia and Arcobacter presented antimicrobial resistance to the drugs under study, as well as T5 (10 µg) to which the two bacteria under study were fully susceptible.